Optimalisasi Media Musikalistik Terapis Sebagai Penyembuhan Diri Pada Anak Keluarga Tak Utuh - Nindya Annisa Salzabila; Memet Sudaryanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
A harmonious family greatly influences a child in carrying out his development both physically and psychologically. However, not all children are born and live in a complete family environment, many children also live and are born from broken homes. This of course has an impact on the lives of broken home children such as lack of affection, not being good at socializing, lack of a support system, and the possibility of experiencing problems in the academics they take. Therefore, a solution is needed for children by applying therapy using musicality media or media results from a combination of therapy by listening to music that forms a person's psyche accompanied by poetry writing activities. The purpose of this study is to explain the optimization of the therapist's musicality media as a self-healing solution for broken home children. This research method uses clinical language therapy with magical musik sung by Indonesian singers. To answer this problem, this study uses a qualitative approach by examining the tone content of Indonesian songs and examining the meaning of the songs. After that, clinical testing and interviews were conducted on children with intact families to include the resulting poems. The interview relates to (1) the use of media used to convey the hearts of children with incomplete families; and (2) the form of interaction produced by children in conveying their feelings in writing or verbally. The results showed that optimizing the use of the therapist's musicality media can be used as a self-healing therapist for children from broken homes because music therapists and writing poetry can influence children to express more emotions so that they can ease the psychological burden.